Pulmonary rehabilitation following hospitalisation for acute exacerbation of COPD: referrals, uptake and adherence. Issue 2 (14th August 2013) - Jones, Sarah E; Green, Stuart A; Clark, Amy L; Dickson, Mandy J; Nolan, Ann-Marie; Moloney, Clare; Kon, Samantha S C; Kamal, Faisal; Godden, Joy; Howe, Cathy; Bell, Derek; Fleming, Sharon; et al.
Abstract: Rationale: Several randomised controlled trials support the provision of early pulmonary rehabilitation (PR) following hospitalisation for acute exacerbation of chronic obstructive pulmonary disease (AECOPD). However, there is little real-world data regarding uptake, adherence and completion rates. Methods: An audit was conducted to prospectively document referral, uptake, adherence and completion rates for early post-hospitalisation outpatient PR in Northwest London over a 12-month period. Results: Out of 448 hospital discharges for AECOPD, 90 referrals for post-hospitalisation PR were received. Only 43 patients received and completed PR (9.6% of all hospital discharges) despite a fully commissioned PR service. Conclusions: Despite the strong evidence base, there are poor referral and uptake rates for early outpatient PR following hospitalisation for AECOPD, with only a small proportion of the intended target population receiving this intervention.